2014
DOI: 10.3109/15376516.2014.956915
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of autophagy promotes caspase-mediated apoptosis by tunicamycin in HepG2 cells

Abstract: Tunicamycin (TM) causes accumulation of unfolded protein in endoplasmic reticulum (ER) lumen and introduces from elsewhere ER stress. This study was to assess the apoptosis and autophagy effect induced by TM on HepG2 cells and the role of autophagy in the system. The viability of HepG2 cells was significantly inhibited by TM in a dose-dependent manner detected by MTT assay. Then, the apoptotic morphology change, increasing apoptotic cell rate suggested that apoptosis was induced by TM in a time- and dose-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…23 Based on the fact that tunicamycin exhibited similar effects as BEZ235 on inhibition of the PI3K/AKT/mTOR signaling pathway and stimulation of apoptosis, it was supposed that both chemicals might share similar mechanisms. With respect to autophagy, a recent study showed that tunicamycin enhanced conversion from LC3I to LC3II (autophagosome-associated form) and increased the Beclin1 levels, 24 which had also been described in this study. Further studies had illustrated that ERS increased autophagy, apoptosis, and chemotherapy resistance of MCF-7 cells via inhibition of the PI3K/AKT/mTOR signaling pathway.…”
Section: Discussionmentioning
confidence: 68%
“…23 Based on the fact that tunicamycin exhibited similar effects as BEZ235 on inhibition of the PI3K/AKT/mTOR signaling pathway and stimulation of apoptosis, it was supposed that both chemicals might share similar mechanisms. With respect to autophagy, a recent study showed that tunicamycin enhanced conversion from LC3I to LC3II (autophagosome-associated form) and increased the Beclin1 levels, 24 which had also been described in this study. Further studies had illustrated that ERS increased autophagy, apoptosis, and chemotherapy resistance of MCF-7 cells via inhibition of the PI3K/AKT/mTOR signaling pathway.…”
Section: Discussionmentioning
confidence: 68%
“…strated by the (a) disappearance of ER stress by 6 weeks when ER autophagy was active; (b) marked reductions in ER levels of TG and DG by 6 weeks compared with levels at 3 weeks; and (c) persistence of ER stress and the appearance of several markers of apoptosis, including cleaved caspase 12, which has been shown to be specifically induced by ER stress (42), when initiation of autophagy was blocked by ATG7 ASO treatment. The increased FA oxidation we observed when autophagy was blocked and which, like autophagy, prevented steatosis in the apoB ASO-and ATG7 ASOtreated mice, very likely resulted from lipids released directly from "sick" ER; we will attempt to better characterize this observation in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The PARP and caspase have been confirmed to regulate the mechanism of apoptosis. 22,23 The caspase-3 is regarded as the most essential of the executioner caspases, activated caspase-3 can cleave various structural and regulatory proteins, which ultimately lead to the alterations in morphology and biochemistry of apoptotic cells. 24 Caspase-9 is the upstream caspase which is involved in the apoptotic process.…”
Section: Discussionmentioning
confidence: 99%